The bone detectives : how forensic anthropologists solve crimes and uncover mysteries of the dead - Jackson, Donna M., 1959-; Fellenbaum, Charlie (Boston : Little, Brown and Co., 1996)
Explores the world of forensic anthropology and its applications in solving crimes.
Includes index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
8.8
5-8
Keywords: Forensic anthropology -- Juvenile literature; Criminal investigation; Forensic anthropology; Forensic sciences; Criminal investigation; Forensic sciences